Which Pre- and Postoperative Coronal Plane Laxity Parameters Influence Patient Satisfaction and Function after Primary Total Knee Arthroplasty? - McAuliffe, Michael; O'Connor, Patrick; Major, Lisa; Garg, Gautam; Whitehouse, Sarah L.; Crawford, Ross (The Journal of Knee Surgery, 2020)
Soft tissue balancing, while accepted as crucial to total knee arthroplasty (TKA) outcomes, is incompletely defined as the subject of broad recommendations. We analyzed 120 computer-assisted, posterior stabilized TKA undertaken for osteoarthritis. Coronal plane laxity was measured, in the 91 varus and 29 valgus knees, prior to any bone resection or soft tissue release, and again after implant insertion. Soft tissue laxity parameters were correlated to the American Knee Society Score (2011) at a minimum follow-up of 12 months with a focus on patient function and satisfaction. Thirteen specific laxity parameters showed a significant correlation to satisfaction, one parameter correlated to function, and another to both functional and satisfaction outcomes. Most correlations were weak, the strongest related to postoperative decreases in coronal plane laxity. Greater preoperative varus but not valgus deformity was associated with higher satisfaction scores. Additionally, 30 patients who reported 40 of 40 satisfaction and that their TKA knee felt normal at all times did not have soft tissue balancing parameters distinguishing them from other subjects. Patient satisfaction and function outcomes demonstrated limited correlation to coronal plane soft tissue parameters. It appears that optimizing TKA satisfaction and function is not as simple as producing a narrow range of coronal laxity parameters. The ongoing debate around optimal coronal plane alignment and its subsequent effect on coronal plane soft tissues may not be as independently important as currently argued. Soft tissue balance may need to be considered as a more complex global envelope.
Keywords: total knee arthroplasty; ligament balance; posterior stabilized; satisfaction; function